Lattice Boltzmann simulation of mass transfer in thermally driven cavity flows. (1st May 2008) - Yu, Huidan; Zhang, Jinsuo; Li, Ning
We study mass transfer in 2D thermally driven cavity using lattice Boltzmann method. Simulations are performed to investigate various effects on enhancement of oxygen mass transfer in lead/lead bismuth eutectic. It is shown that oxygen transfer is dominated by convection although diffusion plays a role. Comparative studies demonstrate that side heating and top-cooling configuration is more efficient than side-heating/cooling and oxygen transfers more rapidly in a square than rectangular cavity with same area. This work supplies supportive information for developing active oxygen control technique in experiments to prevent or reduce corrosion in liquid metal cooled nuclear reactors.